Genome-scale metabolic modeling reveals specific vaginal Lactobacillus strains and their metabolites as key inhibitors of Candida albicans - Tianqi Hu; Ya Meng; Changying Zhao; Dashuang Sheng; Sijie Yang; Junhui Dai; Tiantian Wei; Yiming Zhang; Guoping Zhao; Yanan Liu; Qinghua Wang; Lei Zhang (Microbiology Spectrum)
ABSTRACT As the predominant constituents of the vaginal microbiome in healthy women, Lactobacillus species are considered essential in maintaining a homeostatic vaginal microbiome. Specific Lactobacillus species can produce beneficial metabolites to support their persistence within the host environment and inhibit Candida albicans colonization. Due to the extensive diversity of Lactobacillus species and their metabolites, comprehensively investigating all possible interactions remains challenging. This study employed an integrative approach combining genome-scale metabolic modeling, metagenomic sequencing, and in vitro validation to explore Lactobacillus and C. albicans interactions. Pairwise simulations of 159 Lactobacillus strains with C. albicans revealed that most strains exhibit inhibitory effects, altering fungal amino acid and carbohydrate metabolism. Key inhibitory metabolites identified included formate, L-lactate, and L-malate. Metagenomic analysis of vaginal swabs from 20 vulvovaginal candidiasis (VVC) patients and 20 healthy women showed a correlation between Lactobacillus species abundance and reduced C. albicans colonization. In vitro experiments confirmed the inhibitory effects of these metabolites and the selected Lactobacillus strains on C. albicans growth, thereby validating our computational predictions. These findings provide insights into the metabolic interactions within the vaginal microbiome and pave the way for targeted microbial or metabolite-based therapeutic strategies to manage VVC.IMPORTANCEVulvovaginal candidiasis is a prevalent fungal infection with significant implications for women’s health, caused primarily by Candida albicans. Although the protective role of a Lactobacillus-dominated vaginal microbiome is well established, the metabolic mechanisms underlying the interactions between Lactobacillus species and C. albicans remain inadequately understood. Specifically, the Lactobacillus species that effectively inhibit C. albicans and the metabolic pathways involved warrant further investigation. This study offers novel insights into the metabolic mechanisms underlying Lactobacillus antagonism against C. albicans. By identifying critical metabolic pathways and inhibitory metabolites, this study enhances our understanding of vaginal microbiome dynamics and host-microbe interactions. The findings suggest that key Lactobacillus strains and their metabolites could significantly reduce harmful levels of C. albicans, paving the way for future therapeutic strategies that leverage these microbial characteristics to promote vaginal health.